Concept of Slowness in Sten Nadolny’s Novels - Strakhova, Irina; Aydarova, Alsou; Mazaeva, Tatyana (Journal of History Culture and Art Research, 2018)
The article studies the concept of slowness in the novelistic work by the contemporary German writer Sten Nadolny. The concept of slowness acquires special significance in the writer’s books both in correlation with the title of the most recognized novel by Sten Nadolny and with respect to the originality of the writing style of the author’s other novels. The aim of the article is to define the specific features of the slowness phenomenon which is the cornerstone for character portrayal in novel creativity of S. Nadolny. The reliability of the research results is based on the analysis of extensive critical and artistic material. The study examines his works «Netzkarte» «Die Entdeckung der Langsamkeit», «Selim oder die Gabe der Rede», and «Weitlings Sommerfrische». The research employed descriptive and cultural-historical methods. The authors come to the conclusion that slowness is the main component of the character portrayal in the novel and serves as a means of more expressive realization of the author's philosophy of slowness.